Correlation of shoulder and elbow kinetics with ball velocity in collegiate baseball pitchers - Post, E. G.; Laudner, K. G.; McLoda, T. A.; Wong, R.; Meister, K. (Journal of Athletic Training, 2015)
Context: Throwing a baseball is a dynamic and violent act that places large magnitudes of stress on the shoulder and elbow. Specific injuries at the elbow and glenohumeral joints have been linked to several kinetic variables throughout the throwing motion. However, very little research has directly examined the relationship between these kinetic variables and ball velocity.